Bob Su on Humanity, Communities, Minds, Perceptions and Knowledge on Ice - Su, Dr. Bob (2011)
Dr. Bob Su, Department of Water Resources at University of Twente, Netherlands, TBC, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.